Identification of interactions between multiple components in Socheongryong-tang using a plant profiling approach - Oh, Hyun-A; Lee, Hyunbeom; Kang, Keon Wook; Im, Ji Hye; Kim, Donghak; Yang, Hyun Ok; Jung, Byung Hwa (WILEY, 2019)
Traditional herbal medicine consists of multiple components. There are interactions among the components, which affect both potency and toxicity. The preparation of herbal medicines can be a cause of interactions between multicomponents in herbs. To demonstrate the differences in multiherb interactions based on the preparation methods, the changes in the active components in the different preparations of Socheongryong-tang (SCRT) were evaluated using metabolomics profiling. We performed multicomponent profiling of the decoction of SCRT (SCRTD) and individual herb mixture (SCRTM) using ultra-high-performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry (UPLC-QTOF-MS). Active compounds from SCRTD and SCRTM were identified using multivariate analysis, and the activities between the two groups were compared. We also evaluated the anti-inflammatory effect of SCRT through investigating the protein expression of iNOS and COX-2 in lipopolysaccharide-induced macrophage RAW 264.7 cells in both groups. From the multivariate analysis, 53 active compounds that have different intensities between SCRTD and SCRTM were identified. The intensities of those components, such as ephedrines, glycyrrhizic acid, 6-gingerol and (2E,4E,8Z,10E)-N-isobutyl-2,4,8,10-dodecatetraenamide, which is newly identified in Asiasarum heterotropoides, were mostly higher in SCRTD than in SCRTM, which was related to the anti-inflammatory effect. From the iNOS inhibition test, it was found that SCRTD had a stronger anti-inflammatory effect than SCRTM. It was demonstrated that multicomponent interactions can be changed by the preparation method, and finally the anti-inflammatory effect in SCRT can be affected.
Keywords: TRADITIONAL CHINESE MEDICINE; QING-LONG-TANG; ANTIINFLAMMATORY ACTIVITY; PAEONIA-LACTIFLORA; MASS-SPECTROMETRY; CINNAMOMUM-CASSIA; CONSTITUENTS; INFLAMMATION; SCHISANDRIN; INHIBITION